2022
DOI: 10.1039/d2nj00984f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically reconstructed high-entropy amorphous FeCoNiCrVB as a highly active oxygen evolution catalyst

Abstract: Designing catalysts with highly electrochemical activity and stability for oxygen evolution reaction (OER) is a pivotal step for sustainable water splitting. Interface engineering can reach a practical approach to enhance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[ 40,41,47 ] In addition, recent literature report showed that surface reconstruction for HEO system can happen under electrochemical activation or during OER. [ 23,57–59 ] All our synthesized HEO catalysts, regardless of their alloying order (ternary, quaternary, quinary, or senary), showed a significantly higher OER activity compared to state‐of‐the‐art commercial IrO 2 catalyst. More detailed investigations of the catalyst's stability and the mechanism behind the activity enhancement will be discussed in the following sections.…”
Section: Resultsmentioning
confidence: 94%
“…[ 40,41,47 ] In addition, recent literature report showed that surface reconstruction for HEO system can happen under electrochemical activation or during OER. [ 23,57–59 ] All our synthesized HEO catalysts, regardless of their alloying order (ternary, quaternary, quinary, or senary), showed a significantly higher OER activity compared to state‐of‐the‐art commercial IrO 2 catalyst. More detailed investigations of the catalyst's stability and the mechanism behind the activity enhancement will be discussed in the following sections.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, post-OER characterisation is important to understand the dynamic changes of HEM catalysts and correlate such changes with the catalyst's stability. Zhong et al reported that upon pre-activation during OER, soluble Cr +6 and V +5 species formed in FeCoNiCrVB HEA catalysts, which led to the leach of Cr and V in the subsequent OER process [210]. In addition, for FeMnCoCrNi HEA catalysts [214], it was also reported that no Cr signal was detected by energy-dispersive spectroscopy or XPS after the OER stability test in 0.1 M KOH at 100 mA cm −2 for 60 h, indicating a remarkable compositional change upon OER.…”
Section: Post-oer Characterisation Of Hem Catalystsmentioning
confidence: 99%
“…In addition to the crystalline structure, the high-entropy concept has also seen applications in amorphous materials. [63,[67][68][69][70][71][72][73] Metallic glasses, one type of alloys with a disordered, amorphous microstructure, can provide tunable catalytic performance based on the individual properties of incorporated metals. Designing high-entropy metallic glasses may offer access to electrocatalytic properties arising from the dissimilar metal interactions.…”
Section: Other Types Of High-entropy Materialsmentioning
confidence: 99%
“…High-entropy amorphous alloys and oxides are also good candidates for the electrochemical water splitting. [70][71][72][73] High-entropy amorphous FeCoNiCrVB alloy was subject to surface reconstruction by means of cyclic voltammetry (CV) to cause selective leaching of metal elements, formation of oxyhydroxide active species, and introduction of core-shell nanoparticles, which facilitated mass/electron transfer at the catalyst interface and promoted the OER catalysis. [70] A similar electrochemical activationinduced surface reconstruction was also observed on a highentropy amorphous FeCoNiMnBO x oxide, which formed a stable oxyhydroxide surface layer that contributed greatly to the OER performance.…”
Section: Other Types Of High-entropy Materialsmentioning
confidence: 99%